The inclusion of cultural diversity in higher education curriculum design. - Abdul Rahman, Shukran; Alwi, Azlin (2018)
This paper reports findings of a study that assesses the measures taken by universities in selected South East Asian countries when developing the competencies of students from other countries. This is to address the internationalization thrust of higher education (HE) that constitutes the participation of international students and academics in HE-related activities. Specifically, this study assesses whether the academic programs (a) suit students’ diverse backgrounds; and (b) address the cultural background from where the international students come from. Four participants from four different countries participated in this study. Two were HE academic leaders, researcher, and university leader; one was HE researcher and academic; while another was an academic. The data were collected through online in-depth interviewing conducted via email. The results revealed that majority of them perceived that cultural background was not addressed in the academic programs. However, certain courses in the HE institutions did address the host countries’ cultural beliefs and traditions. The findings are discussed in the context of higher education institution to enlighten universities and higher education authorities on the appropriate method to design curriculum in universities hosting international students.